2013
DOI: 10.1146/annurev-biochem-072711-163904
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Chaperones and Proteostasis

Abstract: There is a family of currently untreatable serious human diseases that arise from the inappropriate misfolding and aggregation of extracellular proteins. At present our understanding of mechanisms that operate to maintain proteostasis in extracellular body fluids is limited but has significantly advanced with the discovery of a small but growing family of constitutively secreted extracellular chaperones (ECs). The available evidence strongly suggests that these chaperones act as both sensors and disposal-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
173
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 161 publications
(181 citation statements)
references
References 244 publications
(214 reference statements)
6
173
0
Order By: Relevance
“…It is well-established that molecular chaperones are vitally important for targeting misfolded proteins for repair or degradation within cells (12), and it is becoming increasingly apparent that extracellular chaperones, including α 2 M, also participate in essential proteostasis systems that function outside of cells (11). It has been shown that hypochlorite generated by stimulated neutrophils induces dissociation of α 2 M in vitro (26), and increased oxidation of α 2 M has been detected in rheumatoid ar- thritis and Alzheimer's disease (27,44), two protein misfolding conditions in which myeloperoxidase activity is known to be elevated (5, 45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-established that molecular chaperones are vitally important for targeting misfolded proteins for repair or degradation within cells (12), and it is becoming increasingly apparent that extracellular chaperones, including α 2 M, also participate in essential proteostasis systems that function outside of cells (11). It has been shown that hypochlorite generated by stimulated neutrophils induces dissociation of α 2 M in vitro (26), and increased oxidation of α 2 M has been detected in rheumatoid ar- thritis and Alzheimer's disease (27,44), two protein misfolding conditions in which myeloperoxidase activity is known to be elevated (5, 45).…”
Section: Discussionmentioning
confidence: 99%
“…10). Furthermore, α 2 M has been identified as one of a small number of abundant extracellular chaperones (11). Although our understanding of extracellular proteostasis has increased in recent years, it is still limited compared with our extensive knowledge of the mechanisms comprising intracellular proteostasis (12).…”
mentioning
confidence: 99%
“…Molecules with chaperone activity are key components of the quality control processes used by living systems to maintain protein homeostasis in the highly crowded cellular environment. The majority of chaperones are located within cells Hartl et al, 2011;Bukau et al, 2006), but the presence of protective guardians in the extracellular environment collectively referred to as extracellular chaperones is now widely acknowledged (Wyatt et al 2012;Wyatt et al, 2013). Typically, chaperones prevent the aggregation of unfolded polypeptide chains ("holdase" activity) and/or promote their de novo protein folding or refolding, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…88,89 Another fascinating aspect of ECs and extracellular proteostasis is that of an extracellular protease machinery. Wyatt et al 90 in several of their review articles have discussed about the role of an extracellular protease machinery in protein quality control mechanism at the extracellular space. In case of neurons, a major role of extracellular space involves the maintenance of a normal neuronal structure for effective signal generation and transduction along with coordinated synaptic transmission of the neuronal signals.…”
Section: Ecs In Ameliorating Cns Amyloidosismentioning
confidence: 99%